ALL-RUSSIAN RESEARCH AND PRACTICE CONFERENCE «PHARMACOTHERAPY AND DIETETICS IN PEDIATRICS» WITH INTERNATIONAL PARTICIPATION 17-19 SEPTEMBER 2012, KRASNOYARSK - Article Editor (Union of pediatricians of Russia, 2012)
.